Comparison between spoken and sing language features in heritage and modern lesson - Badi, Ali Muhsen (Al-Adab Journal, 2019)
The communicative media have occupied a large space in the humans thinking since the first stage of his/her consciousness of these media and their effects on the life . Although spoken language was the center of systematic attention and attracted a lot of linguistic efforts, unfortunately the other types of communicative media didn’t take a great deal of attention and on the top of these media is the sing language either natural or artificial on . The object of the study is to display the efforts on sing language when it is associated with spoken language . The main object of this study is to observe the ancient and modern scientific achievement which is limited to the balance between spoken and sign language and the results of these efforts because the detailed information that had been included between spoken and sign language represent the core that can be concluded of independent studies.